Analysis of the Private, Collective, and Relational Self-Cognitions among Han and Tibetan Chinese. Issue 1 (August 2014) - Huang, Wei; Mamat, Marhaba; Shang, Rui; Zhang, Tianyang; Li, Hao; Wang, Yao; Luo, Wei; Wu, Yanhong
Differences in the concepts of private, collective, and relational selves between two Chinese ethnic groups, the Han and Tibetan—adhering to the philosophies of Confucianism and Tibetan Buddhism, respectively—were examined. 128 students (54 men, 74 women; M age=20.9 yr., SD = 2.2) completed the revised Twenty Statements Test and self-reference paradigm. Study 1 found that for Han participants relational and private selves were ranked similarly and as more important than the collective self. Studies 2 and 3 found that adjective words describing private and relational selves were recalled in greater proportions than words describing the collective self. Tibetan participants showed no significant differences between the three self-cognitions. The findings correspond to differences in self-identity among these two subcultures.